Budget structure and reelection prospects: Empirical evidence from French local elections - Aurélie Cassette; Etienne Farvaque; Jérôme Héricourt; Nicolas Jean (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2009)
This paper is a study of the influence of economic and political conditions on the results of incumbent parties' candidates in local elections in France. The large sample used covers 586 towns and two elections (2001 and 2008). It explicitly deals with the specificities induced by the tworound process of the French electoral rule, and results are provided for both the reelection probability and the share of votes. It is shown that the budget structure, and notably equipment expenditures, has a strong impact on the incumbent party's share of votes. Political variables also play a role, as do the number of candidates, and national partisan waves.
Keywords: D72; H72; H76; 330; Local elections; Visible expenditures